Suicidality in Obsessive-Compulsive Disorder: Prevalence and Relation to Symptom Dimensions and Comorbid Conditions - Torres, Albina Rodrigues [UNESP]; Ramos-Cerqueira, Ana Teresa A. [UNESP]; Ferrao, Ygor A.; Fontenelle, Leonardo F.; do Rosario, Maria Conceicao; Miguel, Euripedes C. (Physicians Postgraduate Press, 2011)
Background: Suicidal thoughts and behaviors, also known as suicidality, are a fairly neglected area of study in patients with obsessive-compulsive disorder (OCD).Objective: To evaluate several aspects of suicidality in a large multicenter sample of OCD patients and to compare those with and without suicidal ideation, plans, and attempts according to demographic and clinical variables, including symptom dimensions and comorbid disorders.Method: This cross-sectional study included 582 outpatients with primary OCD (DSM-IV) recruited between August 2003 and March 2008 from 7 centers of the Brazilian Research Consortium on Obsessive-Compulsive Spectrum Disorders. The following assessment instruments were used: the Yale-Brown Obsessive Compulsive Scale, the Dimensional Yale-Brown Obsessive Compulsive Scale, the Beck Depression and Anxiety Inventories, the Structured Clinical Interview for DSM-IV Axis I Disorders, and 6 specific questions to investigate suicidality. After univariate analyses, logistic regression analyses were performed to adjust the associations between the dependent and explanatory variables for possible confounders.Results: Thirty-six percent of the patients reported lifetime suicidal thoughts, 20% had made suicidal plans, 11% had already attempted suicide, and 10% presented current suicidal thoughts. In the logistic regression, only lifetime major depressive disorder and posttraumatic stress disorder (PTSD) remained independently associated with all aspects of suicidal behaviors. The sexual/religious dimension and comorbid substance use disorders remained associated with suicidal thoughts and plans, while impulse-control disorders were associated with current suicidal thoughts and with suicide plans and attempts.Conclusions: The risk of suicidal behaviors must be carefully investigated in OCD patients, particularly those with symptoms of the sexual/religious dimension and comorbid major depressive disorder, PTSD, substance use disorders, and impulse-control disorders. J Clin Psychiatry 2011;72(1):17-26 (C) Copyright 2011 Physicians Postgraduate Press, Inc.